Rice genotypes (Oryza sativa) respond to varying planting dates and environmental conditions - 1Asif Ali Kaleri, 1Danish Manzoor,1Rabia Laghari,2Muzamil Awan, 3Bina Khanzada, 4Hafsa Munir, 2Saba Solangi, 2Tameer Hyder Shah.5Ameer Jan, 6Laiba Ashfaq, 2Ghulam Sajjad Kaleri Kaleri (Kashmir Journal of Science)
An essential food crop with a big role in the global economy is rice (Oryza sativa L.). In terms of production, it comes in third place worldwide, behind maize and wheat. Additionally, about two-thirds of the world's population depends mostly on rice as a food source. The sowing date significantly impacts the productivity of rice. The performance of rice is significantly improved when it is sowing in ideal conditions, which include suitable soil and air temperatures and sufficient soil moisture. However, planting rice too early exposes it to cold conditions, which can lead to low vigour, poor germination, and even seedling death. On the other hand, planting rice too late might result in lower yields and lower-quality grains since the rice grain's essential reproductive phase corresponds with the hottest part of the summer. The SAU Tando Jam served as the field trial site in 2022's Khaif season. A split plot design was employed to set up the experiment. The main plots are divided into three planting dates: June 30, July 15, and July 30. Subplot treatments included four rice genotypes: N-M-11, N-M-8, N-M-10, and KSK-33 (control). On the other hand, rice crops planted on June 30th performed significantly higher than those planted on the other dates. The crops had the following traits: a 97.27 cm plant height, an average of 19.18 tillers per plant, a 20.11 cm panicle length, a 29.82 g seed index, 8964 kg/ha of biological yield, 5330 kg/ha of grain output, and an 84.11% harvest index. The interaction of genotype and sowing date was found to significantly influence plant height, panicle length, number of shoots per plant, seed index, biological yield, grain yield, and harvest index. When seeded on June 30th, the genotype N-M-11 showed the greatest values for these parameters.